OLAHRAGA BULUTANGKIS SEBAGAI MEDIA INTERAKSI SOSIAL DAN RELAKSASI STRES BAGI USIA DEWASA DI PB. BOA KABUPATEN BATANG - Nikmah, Bakhirotun; Qoriah, Anirotul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the role of badminton as a medium for social interaction and to examine its effectiveness in reducing stress among adults in the Persatuan Bulutangkis (PB) BOA, Batang Regency. This study employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. This sampling technique used is purposive sampling involving five active partcipants. Data validty is ensured through source and method triangulation, while data analysis includes data reduction, data presentation, and conculasion drawinh. The results indictae that badminton activities play a significant role in fostering social interaction, strengthening relationships among participants, and creating a positive social environment. Additionally, the activity is proven to reduce stress levels, as participants reported feeling more relaxed, refreshed, and mentally relived after enganging in the activity. This release of endorphins during ecercise contributes to improved mood and psychological well-being. Therefore, badminton can be considered an effective medium for stress relaxation among adults.